Analisis Pengaruh Dimensi Word Of Mouth Communication Terhadap Keputusan Pembelian Sajian Kuliner Lapak Angkringan (Studi Pada Konsumen Penikmat Sajian Kuliner Lapak Angkringan Di Wilayah Mangkubumi Yogyakarta) - Hendarwati, Atik (Akmenika, 2015)
This study aims to analyze the influence of marketing communication by word of mouth of âangkringanâ culinary offerings in Mangkubumi area, Yogyakarta. The research data consists primary and secondary data. Research period start on December 2014 until February 2015. The samples consist one hundred respondents. Sampling method is non-probability sampling, with the convenience sampling technique. The research variables are dependent variable (Y) consumer buying decisions, Keputusan Pembelian and five independent variables, namely: WOM-Talkers (X1), WOM-Topics (X2), WOM-Tools (X3), WOM-Taking Part (X4) and WOM-Tracking (X5). The results shows that the coefficient of determination (R2) is 47.30%. It means that the amount of variation in the percentage of Keputusan Pembelian can be explained by five independent variables 47.30% while the remaining 52.70% is explained by other causes beyond the model. The results of t-test shows that there are only two independent variables (WOM-Talkers and WOM-Topics) has a significant influences on Keputusan Pembelian while three other independent variables (WOM-Tools, WOM-Taking Part and WOM-Tracking) does not have a significant influences on Keputusan Pembelian on âangkringanâ culinary offerings in Mangkubumi area, Yogyakarta.